2010
DOI: 10.1177/0013164410387336
|View full text |Cite
|
Sign up to set email alerts
|

Item Selection Criteria With Practical Constraints for Computerized Classification Testing

Abstract: This study compares four item selection criteria for a two-category computerized classification testing: (1) Fisher information (FI), (2) Kullback—Leibler information (KLI), (3) weighted log-odds ratio (WLOR), and (4) mutual information (MI), with respect to the efficiency and accuracy of classification decision using the sequential probability ratio test as well as the extent of item usage. The comparability of the four item selection criteria are examined primarily under three types of item selection conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…The results given in Table 1 and Figures 1-4 clearly show that SPRT improves test efficiency by shortening the test length by 19.6% without losing much capacity to maintain high classification accuracy, which is 93.7% here. A similar conclusion that SPRT tends to gives a better performance in CCT can be found in other work (Babcock & Weiss, 2009;Lin, 2011;Thompson, 2009) as well. Thus, SPRT is shown to be an efficient classification method which is used in simulations 2 and 3 for a further evaluation of the LA-CB methods.…”
Section: Results Of Simulationsupporting
confidence: 87%
“…The results given in Table 1 and Figures 1-4 clearly show that SPRT improves test efficiency by shortening the test length by 19.6% without losing much capacity to maintain high classification accuracy, which is 93.7% here. A similar conclusion that SPRT tends to gives a better performance in CCT can be found in other work (Babcock & Weiss, 2009;Lin, 2011;Thompson, 2009) as well. Thus, SPRT is shown to be an efficient classification method which is used in simulations 2 and 3 for a further evaluation of the LA-CB methods.…”
Section: Results Of Simulationsupporting
confidence: 87%
“…In contrast to conclusions from our second simulation, many authors still take for granted the oft-repeated maxim that items should be selected by only considering the classification bound/bounds (e.g., Eggen, 2011;Finkelman, 2008a;Huebner, 2012;Lin, 2011;Lin & Spray, 2000;Wiberg, 2003). Up until now, this maxim was based on logically sound reasoning.…”
Section: Resultsmentioning
confidence: 75%
“…Note that Equation 23 is similar to Equation 21 with p j ðŷ i Þ replaced by p j ðy 0 þ dÞ. Although KL divergence uses a version of the SPRT-based loglikelihood ratio, researchers have found that selecting items by maximizing KL divergence does not result in shorter nor more accurate classification tests than selecting items by maximizing FI at y 0 (e.g., Eggen, 1999;Lin, 2011;Lin Nydick & Spray, 2000). A common complaint in using pointwise KL divergence to select items in CCT is the lack of symmetry between KL j ðy u jjy l Þ and KL j ðy l jjy u Þ.…”
Section: Simulationmentioning
confidence: 99%
“…Chen, Ankenmann, and Chang (2000) used KL information in the early stage of CAT. Eggen (1999) and Lin (2011) have applied KL information to computerized classification testing. Henson and Douglas (2005) proposed KL-based divergence indices to assemble cognitive diagnostic tests.…”
Section: Methodsmentioning
confidence: 99%